CK-MB activity, any additional benefit to negative troponin in evaluating patients with suspected acute myocardial infarction in the emergency department - Veeravich Jaruvongvanich (2018)
© 2015, Medical Association of Thailand. All rights reserved. Background: Coronary heart disease is now the leading cause of death. Diagnosing myocardial infraction (MI) needs cardiac marker in case of equivocal clinical presentations and EKG interpretations. Troponin yields high sensitivity and specificity and could be used as a single screening assay. However, in actual practice, clinicians send CK-MB activity (CKMBa) as a combined marker with an expectation of providing additional diagnostic value due to large historical data. Discordant results from both markers lead to unclear management. Our study was to determine whether CKMBa has potential benefit for initial screening of MI in addition to cardiac troponin T (cTpT) in the Emergency Department (ED), and can this marker be safely removed from the routine laboratory panel in the emergency setting in Thailand. Material and Method: We conducted a retrospective cohort single-center study to examine the usefulness of CKMBa in the ED from 907 patients who presented with clinically suspected acute MI, and investigated with both biomarkers (CKMBa and cTpT). In these patients, 97 patients were included in the final analysis as they had negative cTpT associated with positive CKMBa or CKMBa turned to be positive within 24 hours after serial biomarkers measurements. The outcome was assessed by the final diagnosis, the cause of death if patients died during admission, and the 180-day mortality from medical chart review. In patients highly suspected for MI, further investigations were done including echocardiogram, exercise stress test, and coronary angiogram by experienced cardiologists. Results: During the study period, cTpT were sent 1,772 times and most (95.2%) of the samples were associated with CKMBa results. The outcome showed that no one with negative cTpT was diagnosed as MI on a discharge diagnosis. Fourteen patients died during admission. The definitive cause was not defined as MI. The 180-day mortality was zero. During the follow-up, there was no MI suspected issues that needed further cardiac evaluations. The positive predictive value of CKMBa with negative cTpT was 0% (95% CI, 0-0.047). Conclusion: CKMBa added no benefit to cTpT in diagnosing acute MI in ED. Removing CKMBa from emergency panel could be considered.